Investigation of the fatigue modulus decay in cement stabilized base material by considering the difference between compressive and tensile modulus. (30th October 2019) - Lv, Songtao; Yuan, Jiang; Liu, Chaochao; Wang, Jiaqing; Li, Jianglong; Zheng, Jianlong
Highlights: Study fatigue based on modulus decay considering variance of compressive-tensile. A synchronous test method of modulus was used to monitor modulus during fatigue test. The modulus decay mode of tensile and compressive were established and compared. Abstract: The cement stabilized macadam base experiences tensile and compressive stresses simultaneously in the actual pavement structures, resulting in the influence of stress states on fatigue performance. In this paper, the fatigue performance of cement stabilized macadam was analyzed based on modulus decay considering the difference between compressive and tensile modulus. A synchronous measurement method of tensile and compressive modulus, which based on convention four-point bending test, was utilized to measure modulus of cement stabilized macadam during a fatigue test. The four-point bending fatigue test was conducted upon four different stress levels of 0.25 MPa, 0.5 MPa, 1.0 MPa, and 1.5 MPa. The average of 10 closest modulus values nearby the first 1% of fatigue life was adopted to determine the initial modulus. The last 5 cycles before the failure of the specimen in the fatigue test was determined as the critical modulus value. It was observed from the tests results that the critical value of compressive fatigue modulus was 8 times higher than that of tensile fatigue modulus. The initial and critical values of both tensile and compression decreased with the increase of stress levels. Under different stress levels, the modulus decay mode of tensile and compressive modulus was similar, but the decay rates of tensile modulus were higher than that of compressive modulus. Based on the modulus decay mode, the concept of critical failure point was put forward to characterize the fatigue behavior of cement stabilized macadam. During the fatigue process, both tensile and compressive modulus decay presented three stages, i.e. preliminary stage, stable stage, and rapid attenuation stage. The stable stage of tensile modulus was shorter than that of compressive modulus, which means that the primary fatigue damage occurred in the tensile zone.